2021
DOI: 10.1159/000519564
|View full text |Cite
|
Sign up to set email alerts
|

Study of Baicalin toward COVID-19 Treatment: In silico Target Analysis and in vitro Inhibitory Effects on SARS-CoV-2 Proteases

Abstract: Negative impacts of COVID-19 on human health and economic and social activities urge scientists to develop effective treatments. Baicalin is a natural flavonoid, extracted from a traditional medicinal plant, previously reported with anti-inflammatory activity. In this study, we used pharmacophore fitting and molecular docking to screen and determine docking patterns and the binding affinity of baicalin on 3 major targets of SARS-CoV-2 (3-chymotrypsin-like cysteine protease [3CLpro], papain-like protease [PLpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Encouragingly, a recent study identified good binding affinity of baicalin to the major targets of SARS-CoV-2, 3-trypsin-like cysteine protease (3CLpro) and papain-like protease (PLpro), using pharmacophore fitting and molecular docking techniques ( Lin et al, 2021 ). It suggested that baicalin may inhibit proteases and reduce CS through inflammation-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Encouragingly, a recent study identified good binding affinity of baicalin to the major targets of SARS-CoV-2, 3-trypsin-like cysteine protease (3CLpro) and papain-like protease (PLpro), using pharmacophore fitting and molecular docking techniques ( Lin et al, 2021 ). It suggested that baicalin may inhibit proteases and reduce CS through inflammation-related pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the action mechanisms of reported chemical compounds in ARND combating COVID-19 were diverse. Pathway analysis indicated that baicalin (drug 4) has targets in human cells associated with signals of pro-inflammatory cytokines [ 82 ]. The results of prediction by using the Swiss Target Prediction server disclosed that norwogonin (drug 4) and baicalein displayed binding with a high affinity for enzymes associated with pulmonary damage, such as arachidonate 15-lipoxygenase (ALOX15), cycline dependent kinase 1 (CDK1), lysine-specific demethylase 4D (KDM4D), and xanthine dehydrogenase (XDH) [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Quercetin, apigenin, baicalin, luteolin, hesperidin, genistein, proanthocyanidin and eriodictyol have been found to be capable of alleviating oxidative stress in diabetic nephropathy [63]. Incidentally, all the above flavonoid compounds have been reported to bind to SARS-CoV-2 protein components or the receptor hACE2 [54][55][56][64][65][66][67][68][69]. These flavonoids are also antioxidants suggesting a common mode of action in both COVID-19 and diabetes, which in all probability is through reducing oxidative stress.…”
Section: Synergistic Kidney Damage and Morbidity Due To Covid-19 And ...mentioning
confidence: 99%